Surgical success in obstetric fistula repair and associated factors: findings from a retrospective cohort study in Zambia - Mutola, Sianga; Chomba, Bwalya Magawa; Ng, Nawi; Menda, Dhally M.; Louis, Valérie R.; Michael, Lowery Wilson (BMC surgery, 2025)
Background: Obstetric fistulas are common in low-resourced settings, but the factors associated with successful repair remain unclear in Zambia. We assessed the socio-demographics, fistula characteristics, and healthcare factors associated with successful obstetric fistula repair outcomes in Zambia. Methods: Our retrospective cohort study was based on the Zambia Fistula Foundation Treatment Network’s clinical database, including 1439 women who underwent obstetric fistula surgical repairs at hospitals in Zambia between 2017 and 2023. Tanahashi’s Health Services Coverage framework guided the selection of potential factors associated with successful obstetric fistula repair outcomes. We employed Multivariate Imputation by Chained Equations (MICE) before conducting logistic regression analyses. Univariable models, a multivariable model, and marginal probabilities were then fitted to examine the associations between successful obstetric fistula repair outcome, a fistula that is closed and dry, and relevant covariates. Results: Our results showed an overall fistula repair success rate of 88.1%. Patients from the Northern and Muchinga provinces showed 51% (AOR = 0.49, 95% CI = 0.27, 0.90) lower odds of surgical repair success compared to those from Central and Lusaka provinces. Patients with a previous fistula repair had 47% lower odds of success (AOR = 0.53, 95% CI = 0.32, 0.87) than those without. Finally, surgeries rated intermediate in difficulty had 64% (AOR = 0.36, 95% CI = 0.18, 0.70), and those rated difficult had 90% (AOR = 0.10, 95% CI = 0.05, 0.21) lower odds of success than simple repairs. Conclusion: We identified geographic location, previous repair history, and surgical complexity as the factors associated with successful obstetric fistula repair outcomes.
Veröffentlicht: 17. April 2025
Gesehen am 01.10.2025